Soil aggregation and potential carbon and nitrogen mineralization with cover crops under tropical no-till - Rigon, J. P. G. [UNESP]; Franzluebbers, A. J.; Calonego, J. C. [UNESP] (Soil Water Conservation Soc, 2020)
Sustainability of agriculture with no-tillage (NT) production requires appropriate cover cropping and not a simple and random approach of any cover crop species. However, relatively little is known of the long-term soil surface impacts of different cover crops in rotation with soybean (Glydne max) under NT in the tropics. We evaluated the impacts of different cover crops on soil aggregation, soil organic carbon (C) and nitrogen (N) fractions, and soil microbial activity of a Typic Rhodudalf at the end of 12 years under NT in Sao Paulo state of Brazil. Treatments included main plots during the winter dry season (triticale [x Triticosecale] and sunflower [Helianthus annuus]) and subplots during the spring cover crop season (pearl millet [Pennisetum glaucum], sunn hemp [Crotolaria juncea], forage sorghum [Sorghum bicolor], and fallow with occasional chiseling).All eight of these treatments followed soybean in summer. Winter crop treatments had no effect on soil aggregation, but total organic C and N concentrations were greater (p < 0.05) with triticale than with sunflower. Across depths, soil aggregation and soil C and N fractions were generally enhanced when sunn hemp was cover crop than with fallow in the spring.Triticale followed by sunn hemp provided soil cover and fresh mineralizable residue for improving soil quality in this unfertilized (N) soybean-based cropping system. Our results suggest that maintaining soil cover is important to improve soil aggregation and soil C and N fractions, but also the quality of organic inputs determined by cover crop species is an important factor controlling the dynamics of these soil responses.
Keywords: carbon and nitrogen fractions; diversified cropping systems; Oxisol; residue inputs